CONSTRUCTING A POLITICAL LEGACY IN THE NUSANTARA CAPITAL CITY DEVELOPMENT UNDER JOKO WIDODO’S PRESIDENCY (International Journal of Cultural and Social Science, 2026)
The development of the Nusantara Capital City (IKN) is a major national initiative heavily laden with political dimensions regarding power distribution and legitimation. This study aims to examine how the IKN development project is utilized as a vehicle to construct, reinforce, and legitimize the political legacy during President Joko Widodo’s precidency from 2019 to 2024. The research employs a qualitative method utilizing Norman Fairclough’s (1995) Critical Discourse Analysis (CDA) approach to unearth the power relations underlying the texts and contexts of the discourse. The findings indicate that the government massively produces and reproduces narratives such as Indonesia-centric developmental equity, a smart-green city, and the foundation for the "Indonesia Emas 2045" vision as a soft legacy strategy. This construction of meaning operates as a form of subtle power that normalizes the project and suppresses public resistance concerning environmental degradation, agrarian conflicts, and the fiscal burden. In conclusion, this discursive production and reproduction strive to shift the status of IKN from a mere policy option to an absolute, urgent national agenda. This political mechanism effectively locks in the commitment of future, cross-generational administrations to sustain this megaproject.